(untitled) (Książnica Śląska, 2025)
The article discusses the subject of the silesian problems in the work of Rev. Jerzy Szymik from the perspective of post-memory concept, which was defined by Marianne Hirsch as an experience of people growing up in an environment dominated by a narration descending from the times before their birth. The experience was shared by the poet, who had been raised among family stories of the times before his was born. Traits of those memories are present in his poetry, which has become a testify passing the memory heritage to next generations.